2023
DOI: 10.1590/1806-9061-2022-1668
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Heat-Stress-Impaired Immune and Inflammatory Responses of Broilers by Modulating Toll-Like Receptor-4 Signaling Pathway

Abstract: This study investigated the effect of resveratrol on the immune and inflammatory responses and the mRNA levels of splenic toll-like receptor (TLR)-4 signaling pathway-related genes of broilers under heat stress (HS). One hundred and sixty-two birds were allocated to three groups, each with 6 replicates, for 21 continuous days. The three treatments were as follows: the control group (22 ± 1 °C), the HS (33 ± 1 °C for 10 h d -1 and 22 ± 1 °C for the remaining time) group and the HS + resveratrol (400 mg kg -1 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Of the dual immune reactions, the adaptive and innate response, the adaptive reaction is more multifaceted and involves prolonged immunological challenge ( Mashaly et al 2004 ; Amedy et al, 2011 ; Bilal et al, 2021 ; Ringseis and Eder, 2022 ). Serum immunoglobulin G ( IgG ), and secretory immunoglobulin ( SIgA ) were significantly decreased in heat stressed broilers ( Li et al, 2023b ). SIgA and IgG are 2 main kinds of immunoglobulin in chickens that show a role in maintaining immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the dual immune reactions, the adaptive and innate response, the adaptive reaction is more multifaceted and involves prolonged immunological challenge ( Mashaly et al 2004 ; Amedy et al, 2011 ; Bilal et al, 2021 ; Ringseis and Eder, 2022 ). Serum immunoglobulin G ( IgG ), and secretory immunoglobulin ( SIgA ) were significantly decreased in heat stressed broilers ( Li et al, 2023b ). SIgA and IgG are 2 main kinds of immunoglobulin in chickens that show a role in maintaining immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the harmful effects of HS on immunological responses ( Amedy et al, 2011 ; Farag and Alagawany, 2018 ; Sun et al, 2023 ). HS is responsible for inhibiting the phagocytic activity of leukocytes and suppressing the biosynthesis of B and T lymphocytes ( Li et al, 2023b ). The heterophil to lymphocyte ratio ( H/L ratio) is a popular signal of stress in broilers ( Al-Murrani et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%